2003
DOI: 10.1111/1467-8683.00012
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Valuation and Ownership of Listed Firms in China

Abstract: This paper investigates the relationship between firm performance and corporate governance in China. Firm performance is measured by Tobin's "Q", while corporate governance is determined based on ownership structure and concentration. Prior research, in both China and elsewhere, indicates that ownership structure and concentration have a significant impact on firm performance. The paper builds on previous studies by investigating the complex structure of different share classes that are typical of Chinese list… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
70
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(74 citation statements)
references
References 36 publications
(41 reference statements)
4
70
0
Order By: Relevance
“…Zouari and Taktak (2014) support the neutrality hypothesis and show that there is no relation between ownership concentration and the financial performance of Islamic banks measured by ROA and ROE. On the corporate level, using a sample of firms listed on the Shanghai and Shenzhen stock markets over the period 1997-1999, Hovey, Li and Naughton (2003 conclude that ownership concentration is irrelevant to firm performance measured by Tobin's Q.…”
Section: The Relationship Between Ownership Concentration and Bank Pementioning
confidence: 99%
“…Zouari and Taktak (2014) support the neutrality hypothesis and show that there is no relation between ownership concentration and the financial performance of Islamic banks measured by ROA and ROE. On the corporate level, using a sample of firms listed on the Shanghai and Shenzhen stock markets over the period 1997-1999, Hovey, Li and Naughton (2003 conclude that ownership concentration is irrelevant to firm performance measured by Tobin's Q.…”
Section: The Relationship Between Ownership Concentration and Bank Pementioning
confidence: 99%
“…listed SOEs for the period 1994-1998 and also found that the state had a negative impact on listed firm performance. Wei and Varela (2003) and Hovey, Li and Naughton (2003) similarly found state ownership had a negative effect on firm value. Similar results were reported by Chen (2001) Gul and Zhao (2001), Gul (1999), Wei, Xie and Zhang (2005) and Xu and Wang (1999 Using a "markets" approach to performance therefore suggests that for the state to continue direct ownership of listed firms in China is not optimal.…”
Section: Empirical Evidencementioning
confidence: 90%
“…The findings in the literature show that ownership structure does significantly influence the performance and value of Chinese firms (Xu & Wang, 1999;Chen & Gong, 2000;Gul & Zhao, 2001;Sun, Tong, & Tong, 2002;Hovey, Li, & Naughton, 2003;Hovey, 2005b). The emphasis in these studies has been on the primary forms of state holdings, along with other ownership types in China.…”
Section: Empirical Evidencementioning
confidence: 99%
“…As state ownership and LP ownership are highly correlated, at -84.98%, the regressions are run separately for them. State ownership has been found to be negatively correlated to performance in the literature (Hovey & Naughton, 2007) (see for example, Chen & Gong, 2000;Gul & Zhao, 2001;Hovey, Li, & Naughton, 2003;Wei & Varela, 2003;Xu & Wang, 1999) , however the influence of state holdings on leverage is unknown. It is expected to be negative as the higher the state ownership, the less availability to equity capital and the higher level of implied guarantee.…”
Section: Equity Ownershipmentioning
confidence: 99%
“…It is expected to be negative as the higher the state ownership, the less availability to equity capital and the higher level of implied guarantee. Prior research on legal person holdings suggests that LP ownership i s positively correlated with performance (Hovey & Naughton, 2007) (see for example, Chen & Gong, 2000;Gul & Zhao, 2001;Hovey et al, 2003;Xu & Wang, 1999), however the influence of state holdings on leverage is unknown. Public Shares is equity ownership of publicly held tradable A-shares.…”
Section: Equity Ownershipmentioning
confidence: 99%